ESTUDO DAS PRÁTICAS DE SUSTENTABILIDADE EM GRANDES EMPRESAS QUÍMICAS NA REGIÃO METROPOLITANA DE CAMPINAS (Gestão & Regionalidade, 2022)
In recent years, society has become increasingly aware of and concerned with the degradation of the environment. In this context, organizations are pressured by increasingly stringent environmental legislation. Thus, relating the company to sustainability is something that is paramount and that values ??the organizational image. But for an organization to be considered sustainable, there must be an interaction between the economic, environmental and social dimensions, something known as the Sustainability Tripod. This article aimed to diagnose the degree of involvement of chemical companies in the Metropolitan Region of Campinas with the issue of sustainability. The research is of a qualitative, descriptive and exploratory nature. Five large companies were surveyed and data were collected in their respective Sustainability Reports. The results of the research showed that the companies put into practice the "Sustainability Tripod" in addition to the advanced understanding about social and environmental issues.
Keywords: Sustainability; Sustainable development; Chemical industry; Metropolitan Region of Campinas